Student Attitudes toward Technology-Mediated Advising Systems - Hoori Santikian Kalamkarian; Melinda Mechur Karp (Online Learning, 2017)
The literature on broad-access colleges suggests that low persistence and completion rates may be improved through better advising that employs a teaching-as-advising approach. While resource constraints have traditionally limited the ability of colleges to reform advising practices, technological advances have made it possible to implement technology-based advising tools, some of which can replace face-to-face services. Using focus group interview data from 69 students at six colleges, this study investigates students’ attitudes toward technology-mediated advising. More specifically, we seek to understand how students’ perceptions and experiences vary across different advising functions. We find that students are open to using technology for more formulaic tasks, such as course registration, but prefer in-person support for more complex tasks, such as planning courses for multiple semesters and refining their academic and career goals.